O Pólo industrial de Manaus como modelo de desenvolvimento econômico avaliado sob o enfoque da Lei de Kaldor-Verdoorn - SILVA, Renilson Rodrigues da (2006)
This study aims to analyze and measure the dynamic economy of Manaus Industrial Pole as a development model under the conditions advocated by Kaldor-Verdoorn Law, which has as one of the focus to analyze the relation between production and productivity, under the conditions advocated by Kaldor-Verdoorn Law applied to industries of Manaus Industrial Pole. The Kaldor-Verdoorn Law proposes that theres a trend to productivity growth as long as production grows. Economies of scale are generated in an endogen way by technical change and technological learning (learning by doing), which is a resulted of the demand growth that allows the exploitation of the dynamics economies of present scale mainly, in the manufacturing sector. Based on this statement, total productivity of factors and the partial productivity are estimated. The dynamic of this economy is analyzed through empirically related to the Industries production and performance from January of 1995 to December of 2004 through an Error Correction Model, Granger Causality Test and Structural VAR Model. The Results indicates a reasonable degree of dynamism in this economy, because of the effect combination of short and long term made possible the productivity growth in an accelerated rhythm with quick answers in a short term of productivity under changing shocks in production and employment total values. Shows also the existence of endogenous sources of growth productivity, showing in evidence the crescent scale economies.